Boda-boda Business Activity and Socioeconomic Transformation in Wakiso District, Uganda - Henry Stanley Mbowa; Marus Eton; Sylivia Byarugaba Tushabe (Goodwood Publishing, 2025)
Purpose: This study established the effect of Boda-boda Business Activity (BBA) on socioeconomic transformation in Wakiso District, Uganda. Methods: This study employed a descriptive design with quantitative and qualitative approaches. A total of 89 respondents were determined from 114 people at the boda-boda stage in Kitemu. Questionnaires and interviews were used to collect data. The data were analyzed using SPSS to generate descriptive statistics. SEM was employed to establish the causal effect between the variables. Results: The results indicated that people joined BBA to earn a living to support their families (Mean=4.4; Std.D=0.756), due to a lack of jobs (Mean=4.07; Std.D=1.055), and ease of repairing motorbikes (Mean=3.85; Std.D=1.417). Furthermore, BBA had a significant effect on socioeconomic transformation (?=0.392; p?0.000). Conclusion: The BBA has the potential to bring substantial socioeconomic transformation, including employment creation (mean=4.0), improved mobility (mean=4.12), and stimulated local commerce (mean=3.79) in Kitemu Ward. Thus, the BBA had a positive effect on socioeconomic transformation (?=0.392, p<0.001). Limitation: The study employed a descriptive survey design on motorbike riders in Kitemu Ward, which might hinder generalization of the study findings. Thus, more studies need to be conducted using different research designs on a larger sample of boda-boda stages in Wakiso. Contributions: This study provides information to the Ministry of Work and Transport on how the boda-boda sector can be improved to enhance socioeconomic transformation in Wakiso.